Ketidakstabilan Makroekonomi dan Modal Sosial Islam sebagai Penentu Jangka Panjang Pertumbuhan Fintech Syariah di Indonesia: Analisis Pengujian Batas ARDL - Abdul Aziz; Yusuf Al Manaanu; Suhendri Suhendri; Widiyanti Sukma Dewi; Mutiara Ramadhanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the long-run determinants of Islamic fintech asset (AFS) growth in Indonesia using quarterly data from 2019Q1 to 2025Q4 (T=28) within the framework of ARDL bounds testing. The model includes macroeconomic proxies (inflation, BI interest rate) and indicators of Islamic social capital (Sharia Financial Literacy Index, ILKS; Sharia Financial Inclusion Index, IIKS). The unit root test confirms integration of order I(0) or I(1). The bounds test (F=30.172) rejects the null hypothesis of no cointegration, thereby establishing a stable long-run equilibrium. The error correction rate (ECT=−0.6114, p<0.001) indicates that 61.14% of short-run imbalances are corrected within one quarter. ILKS is the only statistically significant long-run determinant (β = +0.0148, p = 0.040), whilst macroeconomic variables and IIKS exhibit effects that are theoretically consistent but not statistically significant. Residual diagnostics and the CUSUM test confirmed the model’s validity across the three macroeconomic phases. These findings position the growth of Islamic fintech as a phenomenon driven by social capital, implying that financial literacy policies are more effective than monetary policies for the sustainable expansion of the Islamic financial sector (AFS).